Analisis Pengaruh Pasar Modal Global Terhadap Perusahaan Start-up Teknologi - J, Jumawan; Diniyah, Ilma; Wulandari, Indah; Nuriah, Selliatun; Sudirman, Muzzaki; Pharonsandika, Immanuel (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
International capital markets are critical for the financing and expansion of technology startups. Startup companies can get the funds they need to expand, innovate, and compete in global markets through Initial Public Offerings (IPOs) and other financial sources. However, there is also a complex and complex relationship between capital markets and digital startups. Capital markets investors often have high standards for growth and profitability, which runs counter to startups' long-term emphasis on innovation and disruption. Global economic trends can also provide new opportunities and difficulties for technology companies, and capital market volatility can have a major impact on the value of startups. Global financial markets provide significant opportunities for startups to obtain funding and spur expansion. However, this is very important for startup companies.